PERBANDINGAN GAMBARAN FOTO POLOS LESI TB PARU AKTIF PADA PASIEN PEROKOK AKTIF DAN NON-PEROKOK DI RSUD DEPOK JUNI 2019 - FEBRUARI 2020 - Annisa Dinda Rachmatya, (2020)
Tuberculosis (TB) is still one of the most common health problems in Indonesia. One of the risk factors for lung TB is smoking. Extensive tissue damage occurs in smokers pulmonary TB patients that can be seen from the radiological examination. This study intended to determine whether there are differences within the radiological finding of active pulmonary TB lesions in active smokers and non-smokers. This study is an observational analytic using a cross-sectional design. The sample was conducted at pulmonary polyclinic RSUD Depok with 56 respondents. Interviews and medical records were used as data collection instruments. The results showed that 25 respondents (44.6%) were smokers. The pulmonary TB lesions were dominated by moderate category as much as 27 respondents (48.2%). The p-value of the bivariate chi-square analysis = 0.016 (95% CI). There is a difference within the radiological findings of active pulmonary TB lesions in active smokers and non-smokers in RSUD Depok.